Gastrointestinal bleeding risk following concomitant treatment with oral glucocorticoids in patients on non-vitamin K oral anticoagulants. Issue 8 (13th August 2021) - Holt, Anders; Blanche, Paul; Zareini, Bochra; Rasmussen, Peter Vibe; Strange, Jarl Emanuel; Rajan, Deepthi; Jensen, Mads Hashiba; El-Sheikh, Mohammed; Schjerning, Anne-Marie; Schou, Morten; Gislason, Gunnar; Torp-Pedersen, Christian; et al.
Abstract : Objective: Gastrointestinal bleeding (GIB) risk in relation to concomitant treatment with non-vitamin K oral anticoagulants (NOAC) and oral glucocorticoids is insufficiently explored. We aimed to investigate the short-term risk following coexposure. Methods: This is a register-based, nationwide Danish study including patients with atrial fibrillation on NOACs during 2012–2018. Patients were defined as exposed to oral glucocorticoids if they claimed a prescription within 60 days prior to GIB. We investigated the associations between GIB and oral glucocorticoid exposure, reporting HRs via a nested case–control design and absolute risk via a cohort design. Matching terms were age, sex, calendar year, follow-up time and NOAC agent. Results: 98 376 patients on NOACs (median age: 75 years (IQR: 68–82), 44% female) were included, and 16% redeemed at least one oral glucocorticoid prescription within 3 years. HRs of GIB were increased comparing exposed with non-exposed patients (<20 mg daily dose, HR 1.54 (95% CI 1.29 to 1.84); ≥20 mg daily dose, HR 2.19 (95% CI 1.81 to 2.65)). 60-day standardised absolute risk of GIB following first claimed oral glucocorticoid prescription increased compared with non-exposed: 60-day absolute risk: 0.71% (95% CI 0.58% to 0.85%) vs 0.38% (95% CI 0.32% to 0.43%). The relative risk was elevated as well: risk ratio of 1.89 (95% CI 1.43 to 2.36). Conclusions: Concomitant treatment with NOACs and oral glucocorticoids was associated with a short-term rate and risk increase of GIB compared with patients only on NOACs. This could have implications for clinical management, necessitating closer monitoring or other risk mitigation strategies during episodes of cotreatment with oral glucocorticoids.